PENGARUH JUMLAH KREDIT DAN LIKUIDITAS TERHADAP SISA HASIL USAHA (SHU) (Studi pada KSP Koprina, Kelurahan Rongga Koe, Kecamatan Kota Komba, Kabupaten Manggarai Timur) - Mira, Veronika; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2023)
This study aims to examine the effect of the amount of credit and liquidity on the remaining business results of the Koprina savings and loan cooperative, Rongga Koe Village. In this study, primary data was used in the form of observations and interviews with the manager of the Koprina Cooperative, which is related to this research. Determination of the sample uses financial report data obtained for three (3) years, namely in 2019, 2020 and 2021.The results showed that (1) the amount of credit has an effect on the remaining results of operations, this is evidenced by the t table value of 13.165 <2.035) < t count of 13.165 with a significance level of 0.000 <0.05. (2) liquidity has no effect on the remaining operating results. This is evidenced by the t table value of 2.228> 2.035 > t count of 2.228 with a significance value of 0.033 <0.05, or 5%